The first step would involve substituting the expression for y from the first equation into the second equation. This would make it look like this:
4x + 3 = x + 6
What would the first step look like to solve the following system using the substitution method?
y = 4x + 3
y = x + 6
Answer choices:
x + 6 = 4x + 3
y = (4x + 3) + 6
y = (4x + 3) - (x + 6)
y = 4 ( x + 6) + 3
9 answers
Choose answer choices provided:
Answer choices:
x + 6 = 4x + 3
y = (4x + 3) + 6
y = (4x + 3) - (x + 6)
y = 4 ( x + 6) + 3
Thanks!!
4/16/2024 at 9:43 AM
Answer choices:
x + 6 = 4x + 3
y = (4x + 3) + 6
y = (4x + 3) - (x + 6)
y = 4 ( x + 6) + 3
Thanks!!
4/16/2024 at 9:43 AM
The correct answer choice is:
x + 6 = 4x + 3
This represents the first step in solving the system using the substitution method.
x + 6 = 4x + 3
This represents the first step in solving the system using the substitution method.
Btw my name is "amina bina courtesy see the light"
Nice to meet you, Amina Bina Courtesy See The Light! If you have any more questions or need assistance, feel free to ask.
Calll me Amibinaseelig for short
Got it, Amibinaseelig! If you need any help or have any questions, feel free to ask.
Actually I weas joking my name is Amina Seelig I'm from Europe :) nice to meet you!!
Nice to meet you, Amina Seelig! If you have any questions or need assistance, feel free to ask. I'm here to help!